Amylase Inhibition and Free Radical Scavenging Activitites of White Saffron Extract and Fractions - Dwiyati Pujimulyani; Wisnu Adi Yulianto; Astuti Setyawati; Seila Arumwardana; Annisa Amalia; Hanna Sari W. Kusuma; Ervi Afifah (Jurnal Teknologi dan Industri Pangan, 2018)
Diabetes is the most common endocrinal disorder characterized by hyperglycemia and long term complications. It has been reported that oxidative stress and excess of free radicals play major roles in diabetes. Development of antidiabetic drugs has been recently emphasized on natural products with less side effect. Antidiabetic activities of white saffron (Curcuma mangga) have been reported. In this study, antiadiabetic activity of four fractions of C. mangga extract (water, hexane, ethyl acetate, buthanol),  white saffron extract and butylated hydroxytoluene/antioxidant standart) was measured by α-amylase activity assay, while antioxidant activity of those fractions was measured using 2-diphenyl-1-picrylhydrazyl scavanger, and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay. These fractions were also compared to antidiabetic drug, acarbose, as control. Ethyl acetate fraction and white saffron extract  showed higher α-amylase inhibitory activity (IC50 = 840,23 dan 363,67  µg/mL) among fractions. Ethyl acetate fraction of C. mangga showed the higher antioxidant activities among fractions as indicated by DPPH activity DPPH (IC50 = 83,95 μg/ mL), and ABTS (IC50 = 27,37 μg/ mL).